Quality E-Wallet Transaction Services for Indonesia's Millennial Student Generation: Layanan Transaksi E-Wallet Berkualitas untuk Generasi Pelajar Milenial Indonesia - Selsapagita, Indah; Sukardi, Budi (Perisai : Islamic Banking and Finance Journal, 2023)
The study aims to determine the influence of the quality of e-wallet transaction services simultaneously on the lifestyle of Solo Raya millennial students and determine the most dominant variables affecting the lifestyle of Solo Raya millennial students. A quantitative approach was used in this study. The study population consisted of millennial students in Solo Raya. The research sampling method was purposive and used predetermined criteria. Data collection techniques included documentation, literature review, and questionnaires. Data analysis using multiple regression techniques. The result of the study is that the quality of e-wallet transaction services simultaneously significantly affects the lifestyle of millennial students in Solo Raya. The most dominant variable affecting the lifestyle of the Solo Raya millennial students was reliability.